Unidad deportiva Pablo Emilio Riveros. (2020)
It is essential to highlight the importance of sport and recreation for all human beings, for this it requires interest and motivation, which are achieved through various aspects such as adequate infrastructure, continuous programs, and trained personnel. It is important The prevention of problems such as drug addiction, alcoholism, sedentary lifestyle and violence, through the practice of sport and recreation in order to generate added value for society, thinking of improving living conditions, are aspects that justify the exploration of other scenarios, currently the municipality does not have adequate spaces to the technical specifications required for high-performance sports and is insufficient due to the growth of the population in recent years. Through the proposal of the Architectural and Urban Design Sports Unit Pablo Emilio Riveros, four covered sports scenarios are proposed: the first is the administrative and sports volume of two and three levels, in charge of providing hierarchy to the image of the project, this being the main access to the Sports Unit. Element consisting of three functional areas: Administrative Area: Space consisting of a lobby, reception, waiting room, administrative offices and offices for personnel in charge of training athletes. The second level has a gym and through this you can access the sports and recreation area. Sports Area: This space has two main stages of boxing and taekwondo where fighting is carried out professionally or as an amateur sport. In addition to the spectator area. Recreation Area: The recreation area is located on the third level, it has a food area and a social area. Second sports stage: it consists of the skating rink, spectators area (stands), reception, lobby, cafeteria, social area, service area and commercial premises for the sale of necessary implements for the practice of this sport. Third sports stage: Basketball courts that have the spectator area (bleachers), service area and commercial premises. Fourth scenario: Olympic swimming pool, diving pool, in addition to this space are the infirmary, service areas and the grandstand area. Fifth sports stage: Soccer fields with bleachers for spectators, commercial premises for the sale of sports equipment and service areas as complementary spaces. The sports unit is not only designed for sports competitions and amateur sports, in addition to this there are a series of spaces for the recreation of people outdoors where they can interact with the natural environment, through squares, amphitheater with areas of exhibition to carry out events that are required, reading area, stretcher area, bio-healthy gym and games area. Spaces designed as an important element to contribute to the index of green areas, recreational areas in order to solve the existing problem. At the urban level, it is proposed to connect three important points of the Municipality: the municipal library, the municipal central park and the intervention area (Pablo Emilio Riveros sports unit) by means of a Bicycle route as an element of mobility with the aim of complementing the municipality's Bicycle network and order the image of the city in this sector, proposing urban furniture and rest areas.